Rethinking policies and possibilities of sustainable solid waste management system of Dhaka City. (30th September 2020) - Jerin, D; Sara, H; Hasan, T; Quayyum, Z
Abstract: Issues: Solid waste management is one of the biggest concerns in Bangladesh, particularly in Dhaka city at present. This paper aims to find the gaps and challenges in solid waste management policies and implementations and thus, gives an insight towards sustainable solid waste management system in the country. Description of the Problem: Improper solid waste management is adversely impacting environmental protection, public health and the control of carbon emissions in Bangladesh. As a result solid waste has become a major area of public policy with growing concern. Lessons: Bangladesh has been experiencing changes in solid waste management since 1983 with the introduction of Dhaka City Corporation Ordinance and later the promulgation of National 3R Policy in 2010. With few exceptions, the overall waste management system cannot be termed as an efficient sequential process of waste minimization, recycling, and disposal based on global standards. Many initiatives are being implemented as part of independent projects by the non-governmental organizations (NGOs) and not always supported by policies. Though the establishment of several secondary transfer stations (STSs) has improved the environmental conditions and cleanliness of the cities, the waste segregation and recycling practices in the pathways from households to landfill do not adhere to the 3R Policy. Both the recyclable and non-recyclable waste are collected and dumped all together at different levels of waste management, i.e. collection from households, dumping at STSs, and later in the landfill without any formal procedures of sorting and recycling. Lack of coordination between implementing agencies is another problem. Conclusions: Absence of sustainable solid waste management policy and proper execution agency are the main obstacles towards a proper waste management system. This problem is huge and should be addressed immediately to protect the environment and ensure better health of the city population. Key messages: Even though the formation of STSs is one of the significant changes in the system nowadays, it is not evaluated or monitored under any specific policy or ordinance. In order to implement the existing policies, adequate funding and monitoring bodies should be introduced to the waste management sector.